Influence of graphene oxide additive on physical, microstructure, adsorption, and photocatalytic properties of calcined kaolinite-based geopolymer ceramic composites - Narumon Lertcumfu (2020)
© 2020 Elsevier B.V. A kaolin-based geopolymer with graphene oxide additions was fabricated. The metakaolin (MK) was derived from heated kaolinite (750 °C for 3 h), and the graphene oxide was synthesized by Hummer's method. The composite samples were fabricated via a geopolymerization process. The influence of the graphene oxide additions (0–10 wt%) on the obtained geopolymer products’ physical, microstructure, and adsorption properties were investigated. The phase formations and microstructures of the studied materials were characterized by several techniques. The results suggest that the obtained samples are a type of 0–3 composite. The adsorption activity of the materials shows that the graphene oxide addition increased the adsorption ability of the studied composites, with removal efficiency for the GP - 10 % GO samples being very high, i.e. ∼ 93 % for methylene blue (MB) solution and 65 % for Cr(VI) tests at the adsorption equilibrium. The graphene oxides also improved the photocatalytic activities of the samples. Based on these results, this composite has potential for water treatment applications.